TRANSFER PRICING IN INDONESIA: LITERATURE ANALYSIS - Isthika, Wikan; Aryani, Y Anni; Setiawan, Doddy (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research aims to present studies regarding transfer pricing or related party transactions in Indonesia. This research explains that 53 articles comprised 33 from 15 accredited national journals (Sinta 2) and 20 from 18 accredited international journals (Scopus). The articles used are from 2002 until September 2023. This research categorized articles into four parts: publication trends, existing research (themes, topics), causes and effects, and future research agenda regarding transfer pricing or related party transactions in Indonesia. Based on the articles on transfer pricing in Indonesia, this research concludes that transfer pricing or related party transactions can be categorized into 2. There are financial variables and corporate governance variables. Previous studies have inconsistent results because of the difference in transfer pricing indicators used.